Chemical storage of wind energy by renewable methanol production: Feasibility analysis using a multi-criteria decision matrix. (15th December 2015) - Matzen, Michael; Alhajji, Mahdi; Demirel, Yaşar
Abstract: This study is for the technoeconomic analysis of an integral facility consisting of wind energy-based electrolytic hydrogen production, bioethanol-based carbon dioxide capture and compression, and direct methanol synthesis. ASPEN Plus was used to simulate the facility producing 97.01 mt (metric tons) methanol/day using 138.37 mt CO2 /day and 18.56 mt H2 /day. A discounted cash flow diagram for the integral facility is used for the economic analysis at various hydrogen production costs and methanol selling prices. The feasibility analysis is based on a multi-criteria decision matrix consisting of economic and sustainability indicators comparing renewable and non-renewable methanol productions. The overall energy efficiency for the renewable methanol is around 58%. Fixation of carbon reduces the CO2 equivalent emission by around −1.05 CO2 e/kg methanol. The electrolytic hydrogen production cost is the largest contributor to the economics of the integral facility. The feasibility analysis based on multi-criteria shows that renewable methanol production may be feasible. Graphical abstract: Highlights: We simulate renewable methanol production from wind-based hydrogen and CO2. Methanol production can fix 1.05 kg CO2 /kg methanol with an energy efficiency of 58%. Economic and sustainability metrics are estimated for the integral facility. We introduce a decision matrix with both economic and sustainability indicators. Renewable methanol may be feasible versus conventional fossil fuel-based methanol.